Current status of severe fever with thrombocytopenia syndrome in China - Zhan, Jianbo; Wang, Qin; Cheng, Jing; Hu, Bing; Li, Jing; Zhan, Faxian; Song, Yi; Guo, Deyin (Virologica Sinica, 2017)
Severe fever with thrombocytopenia syndrome （SFTS） is an emerging infectious disease caused by SFTS virus （SFTSV）. SFTSV is associated with a high mortality rate and has been reported in China, South Korea and Japan. SFTSV undergoes rapid changes owing to evolution, gene mutations, and reassortment between different strains of SFTSV. In this review, we summarize the recent cases and general properties of SFTS, focusing on the epidemiology, genetic diversity, clinical features, and diagnostics of SFTSV in China. From 2010 to October 2016, SFTS cases were reported in 23 provinces of China, with increased numbers yearly. Infection and death cases are mainly found in central China, where the Haemaphysalis Iongicornis ticks are spread. The national average mortality rate of SFTS infection was 5.3%, with higher risk to elder people. The main epidemic period was from May to July, with a peak in May. Thus, SFTS reminds a significant public health problem, and development of prophylactic vaccines and effective antiviral drugs will be highly needed.